Assessment of health and nutritional status of lipid lowering supplement users in Kuala Lumpur - Asma’ Ali; Ng, Guet Kian; Hayati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2018)
The nutritional and health status of dietary supplements users have been widely studied in other countries. However, few studies have examined lipid-lowering supplements users in Malaysia. Findings are inconsistent concerning the effectiveness of lipid-lowering supplements on cholesterol levels. Hence, this study was aimed to determine the health (physical, mental and social levels) and nutritional status (BMI, blood pressure and lipid profile) of lipid lowering supplement users. A cross sectional study of one hundred lipid lowering supplement subjects was conducted; body weight, height, blood pressure and lipid profile were measured. The results found that majority of the supplement users had normal physical, mental, and social health levels and normal level of lipid profiles, except for HDL-c and LDL-c than the non-users. Results also show an association (p<0.005) between lipid lowering groups (fish oil and flaxseed oil, soluble fiber and phytosterol) and body fat percentage (p=0.002). These findings suggest that in general lipid lowering supplements may have beneficial influence on the mental and social health status, and nutritional status (i.e. TC and TG, blood pressure, body fat percentage).